Evaluation of Osteotomy Accuracy and Rotational and Angular Alignment for Cranial Closing Wedge Ostectomy Performed With and Without Alignment Aids. Issue 1 (7th June 2014) - Addison, Elena S.; Emmerson, Terrance D.; de la Puerta, Benito; Groth, Anna; Black, Tony; Smith, Bruce A.; Burton, Neil J.; Toscano, Michael J.; Wallace, Adrian M.
<x xml:space="preserve">Abstract</x> Objective To (1) investigate the use of K‐wires as alignment aids for cranial closing wedge ostectomy (CCWO) and (2) evaluate their effect on osteotomy accuracy and angular/rotational alignment. Study Design Cadaveric study. Animals Cadaveric pelvic limbs (n = 20). Methods CCWO was performed with and without alignment aids on 20 cadaveric pelvic limbs. CT scans were performed pre‐ and post‐operatively to evaluate tibial torsion and valgus/varus deformity. Digital photographs of the ostectomized bone wedges were used to assess divergence of the 2 osteotomies, and the area of the medial and lateral aspects measured to assess osteotomy angulation within the dorsal plane. Results Osteotomy divergence angle, the difference between the area of the medial and lateral aspects of the ostectomized wedges, and the difference between the pre‐ and post‐operative angles of valgus/varus deformity were all significantly smaller for the alignment aid group. The difference in pre‐ and post‐operative tibial torsion was not significantly different between groups. Conclusions K‐wires can be used successfully as alignment aids during CCWO and help to create a significantly more orthogonal osteotomy. This allows a significant reduction in the difference between the preoperative and postoperative angles of valgus or varus, which may reduce the risk of developing a clinically important iatrogenically introduced valgus/varus deformity postoperatively.